Contribution of MMP14-expressing cancer-associated fibroblasts in the tumor immune microenvironment to progression of colorectal cancer - Makutani, Yusuke; Kawakami, Hisato; Tsujikawa, Takahiro; Yoshimura, Kanako; Chiba, Yasutaka; Ito, Akihiko; Kawamura, Junichiro; Haratani, Koji; Nakagawa, Kazuhiko (Frontiers in Oncology, 2022)
Matrix metalloproteinase 14 (MMP14) expression is implicated in progression of colorectal cancer, but its role in the tumor microenvironment (TME) has been unclear. The relevance of MMP14 to colorectal cancer progression was explored by analysis of transcriptomic data for colorectal adenocarcinoma patients (n = 592) in The Cancer Genome Atlas. The role of MMP14 in the TME was investigated in a retrospective analysis of tumor samples from 86 individuals with stage III colorectal cancer by single cell–based spatial profiling of MMP14 expression as performed by 12-color multiplex immunohistochemistry (mIHC). Analysis of gene expression data revealed that high MMP14 expression was associated with tumor progression and implicated both cancer-associated fibroblasts (CAFs) and tumor-associated macrophages in such progression. Spatial profiling by mIHC revealed that a higher percentage of MMP14+ cells among intratumoral CAFs (MMP14+ CAF/CAF ratio) was associated with poorer relapse-free survival. Multivariable analysis including key clinical factors identified the MMP14+ CAF/CAF ratio as an independent poor prognostic factor. Moreover, the patient subset with both a high MMP14+ CAF/CAF ratio and a low tumor-infiltrating lymphocyte density showed the worst prognosis. Our results suggest that MMP14+ CAFs play an important role in progression of stage III colorectal cancer and may therefore be a promising therapeutic target.